Uji Aktivitas Antiinflamasi Fraksi N-Heksana dan Fraksi Etil Asetat Daun Kemiri (Aleurites moluccanus)Terhadap Mencit Putih Jantan (Mus musculus) - Nela Yulia Putri; Ghalib Syukrillah Syahputra; Dhia Suhailah (Pusat Riset dan Inovasi Nasional, 2025)
Inflammation is a common condition that affects everyone and can affect quality of life. Candlenut leaves (Aleurites moluccanus) are known to contain flavonoid compounds, such as swertisin and 2''-O-rhamnosylswertisin, which are thought to have anti-inflammatory activity. This study aims to test the anti-inflammatory activity of candlenut leaves using four treatment groups, namely positive control (sodium diclofenac), negative control (Na-CMC), n-hexane fraction (200 mg/KgBW), and ethyl acetate fraction (200 mg/KgBW). Leg edema volume measurements were carried out periodically for up to 6 hours using a digital caliper. The results showed that the percentage of edema inhibition in the negative control group reached 64.13%, positive control 38.91%, n-hexane fraction 39.99%, and ethyl acetate fraction 39.82%. Although the ethyl acetate fraction showed better anti-inflammatory activity than the n-hexane fraction, its inhibition percentage was still lower than that of the positive control. These findings suggest that candlenut leaves have potential as a source of anti-inflammatory compounds, particularly the ethyl acetate fraction. Further research is needed to evaluate its efficacy and mechanism of action.